Advancements in catalysts, process intensification, and feedstock utilization for sustainable biodiesel production - Ravikumar Jayabal (Results in Engineering)
Biodiesel, a renewable and biodegradable energy source, presents a sustainable alternative to conventional fossil fuels, facilitating the transition towards sustainable energy frameworks. The synthesis of biodiesel is predicated on transesterification, a chemical process that transforms triglycerides into fatty acid methyl esters (FAME) through the utilization of alcohol and catalytic agents. Recent advancements are directed towards enhancing the efficacy of catalysts, optimizing production processes, and broadening the spectrum of feedstock sources. Heterogeneous catalysts, such as calcium oxide (CaO), yield biodiesel outputs ranging from 95% to 98%, demonstrating superior performance compared to homogeneous catalysts regarding reusability and ecological ramifications. Sustainable feedstocks are increasingly identified, including non-edible oils, waste cooking oils, and microalgae, with waste cooking oil achieving a conversion efficiency of 95% to 97% at the cost of USD 200 per ton. In contrast, microalgae can produce as much as 20,000 litres of oil per acre annually, although associated production costs are comparatively elevated. Innovative techniques, encompassing ultrasound- and microwave-assisted transesterification, significantly improve reaction efficiency while consistently maintaining yields exceeding 95%. Prominent challenges persist, including elevated feedstock prices, energy-intensive operational requirements, and the complexities inherent in catalyst recovery. Future investigative efforts should prioritize the integration of renewable energy sources, the application of environmentally benign solvents, and the valorization of glycerol to bolster the sustainability of biodiesel.